Science Environment Technology And Society Based For Disaster Mitigation - Berlian, Timotius; Subiyanto, Adi; Subiakto, Yuli; Wilopo Wilopo (CV. AFDIFAL MAJU BERKAH, 2024)
In facing the large number of disasters in Indonesia, efforts to reduce disaster risk have become a strong foundation for joint efforts. One of the disaster mitigation learning methods developed is the Science Environment Technology and Society (SETS) learning model. Therefore, this research aims to develop natural disaster learning tools with a SETS vision that are integrated in science subjects, implement disaster teaching materials with an integrated Science Environment Technology and Society vision in science subjects, increase the understanding and skills of teachers and students regarding concepts, principles and practicing self-rescue in the event of a natural disaster, and increasing collegiality between lecturers and teachers as well as between teachers in teaching disaster material to students. This multi-year development research (R&D) was carried out in collaboration with teachers in primary and secondary education. The research results are in the form of five learning model features such as: Syllabus, lesson plans, learning methods, teaching materials, as well as techniques and types of assessment developed including science material for grades IV, V, VI primary school and VII, VII, IX secondary school. The five features are packaged in a Guidebook for Teaching Natural Disasters Integrated in Science (for Teachers), a Textbook (for Students) and a supplement in the form of a cartoon comic. The dissemination results show that the learning tools developed are worthy of being given to students, and can increase students' understanding in recognizing and dealing with disaster.